Analysis of Circular Plate Vibrations in a Structure Made of Sandwich Panel - A. S. ALI (Al-Iraqia Journal for Scientific Engineering Research, 2024)
Sandwich panels are essential elements in many structures like space vehicles, airplanes, cars, buildings, bridges, ships, and submarines. This research focuses on analyzing the vibrations of a circular sheet composed of a sandwich panel. The circular sheet in the sandwich panel enhances its impact resistance, providing a significant advantage. A circular sandwich panel with three free states, one supporting support, and two supporting supports was designed with ANSYS software for modeling purposes. Three free boundary conditions, one supported support, and two supported supports were utilized to conduct the analysis in this research. The results obtained for all three conditions were compared. An increase of the sandwich panel thickness core generally does not impact the frequencies of its vibration modes, and this influence diminishes as the number of supports increases. Increasing the thickness of the top layers has a more significant impact on raising the vibration modes frequency of the studied sandwich panel compared to increasing the core thickness. An increase of 4 mm in the tops' thickness raises the frequency of the 10th mode to over 700 Hz. Meanwhile, a 20 mm increase in the core's thickness elevates the frequency of the 10th vibration mode from around 500 Hz to below 600 Hz. If a sandwich panel is supported, increasing the thickness of the upper layer has little or no effect on the frequency of low vibration modes up to the fourth mode. However, starting from the fifth mode, it becomes evident that increasing the thickness directly affects the frequency of vibration modes.